Analysis of Factors Influencing Consumer Behavior Bring Their Own Shopping Bag (Case Study KecamatanTembalang) - Aries Susanty; Dyah Ika Rinawati; Fairuz Zakiah (International Conference on Engineering and Technology Development (ICETD), 2012)
People can start with "bring your own shopping bag" as a green purchasing behavior to build the awareness of reduce the usage of plastic bags in order to protect the environment. There are some predictors that can be influenced the green purchasing behavior, i.e. social influence, environmental attitudes, environmental concern, perceived seriousness of environmental problems, perceived seriousness of environmental behavior, perceived environmental responsibility, concern for self-image in environmental protection, and the government’s role. All predictors not influence directly to the green purchasing behavior. There is one variable that mediating between all predictors with the green purchasing behavior, namely green behavior intention. Besides that, the significant influence of all predictors of green purchasing behavior can be different from one place to another place. Seeing these phenomena, this study aims to determine which predictors that influence the green purchasing behavior of community in the Kecamatan Tembalang to   carrying their own shopping bag which is mediated by green behavior intention. The proposed model that use in this study is tested via a questionnaire collected from 100 respondents. After questionnaire collected, the Partial Least Squares (PLS) approach was used to analyze the research model of this study. The results of this study showed that green behavior intention has significant impact on green purchasing behavior and green behavior intention of peoples in Kecamatan Tembalang is positively influenced by three predictors i.e. of environmental attitudes, perceived seriousness of environmental problems, and concern for self-image in environmental protection. The result of this study also showed that the perception of concern for the environment is influenced by occupation. Finally, based on some predictors that influence green behavior intention of peoples in Kecamatan Tembalang, this study proposes a number of strategies that can reduce plastic bag usage by Tembalang communities, namely: informational strategy, consequence strategy, and structural strategy.